Epidemiological analysis of tuberculosis cases in the health regions of the state of Piauí (Research, Society and Development, 2020)
Objective: To analyze the epidemiological profile of individuals with tuberculosis in the health regions of the state of Piauí through variables such as gender, age, year of occurrence, area of residence, human immunodeficiency virus/tuberculosis co-infection, disease form and closure status in the last three years. Methodology: This is a cross-sectional, retrospective and descriptive epidemiological study, referring to reported and diagnosed cases of tuberculosis in the health regions of the state of Piauí, in the last three years. Data were collected through the Notification Disease Information System and the Unified Health System Informatics Department, from 2016 to 2018. Analyzes were performed using IBM SPSS Statistics for Windows. Results: The number of cases diagnosed during the established period remained constant, in a total of 2.334 cases. Of these, the highest frequency was in males, with 64.41% of cases. The highest number of tuberculosis cases was found to be HIV negative. The age profile that presented the most cases was 45 to 54 years old. Conclusion: Therefore, there is the importance of the study of tuberculosis cases in the health regions of Piauí state, justified by the number of diagnosed cases, the morbidity, mortality and transmission. Thus, we realize the importance of following and putting into practice the World Health Organization's goals for the end of TB, which is to reduce tuberculosis cases by up to 90% and deaths by 95% by the year 2035.